Metal/polymer/metal hybrid systems: Towards potential formability applications - Carradò, A.; Faerber, J.; Niemeyer, S.; Ziegmann, G.; Palkowski, H.
This paper deals with the development, forming and testing of functional three-layered metal/polymer/ metal sandwich sheets - e.g. for automotive applications - in order to tailor them with particularly demanded properties. The sandwich sheets were produced by roll bonding and heating press processes using austenitic highgrade steel and/or aluminium alloy sheets as surface layers. For the cores thermoplastic polymers, with and without fibres for their reinforcement, were employed. The properties of the sandwiches have been studied and compared with similar, industrially produced material available on the market.
Keywords: HYBRID; MECHANICAL PROPERTIES; MECHANICAL TESTING; FORMING